Peningkatan Perilaku Kerja Sama Anak Usia Dini Melalui Metode Diskusi Kelompok di TK Aisyiyah Bustanul Athfal Minasa Upa - Asisa, Nurul; Damayanti, Eka; M. Rusdi; Majid, Ahmad Farham; Kustiah, Sri (KHIDMAH: Jurnal Pengabdian Masyarakat, 2025)
Social development in children, especially in cooperation behavior is very important to be stimulated from an early age, because it is fundamental to children in interacting with people around them. fundamental in children in interacting with people around them. This service aims to determine cooperative behavior after applying the group discussion method to children aged 5-6 years. This community service research in the form of service learning was carried out at the Aisyiyah Bustanul Athfal Minasa Upa Kindergarten, Makassar City with a total of 10 children participating. The instruments used were an animal size sorting activity worksheet, an observation sheet on the achievement of children's cooperative behavior and an evaluation sheet on the implementation of the intervention. Data were analyzed using descriptive statistics. The results of the service show that children are able to increase cooperative behavior in groups. The findings in this service show that the application of the group discussion method is effective in stimulating social interaction and collaboration among children which is the basic foundation for working together and improving their social skills in the future.